PENDIDIKAN INKLUSI DALAM MEMAJUKAN PENDIDIKAN NASIONAL - I Nyoman Temon Astawa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Inclusion education has more in common with the concepts underlying 'Education for All', and 'School quality improvement'. Furthermore, it is also said that inclusive education is a shift from anxiety about a particular group to an effort that is focused on overcoming obstacles to learning and achievement. Improving the quality of education is one of the main pillars of development in education in Indonesia. Quality education will produce intelligent and competent human resources.